Implementation of CSR Programs by Tjoekir Sugar Factory Towards the Welfare of Cukir Village Community - Ferdiyansyah, Muhammad; Yasin, Ach. (Universitas Negeri Surabaya, 2025)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR) programs carried out by Pabrik Gula (PG) Tjoekir and their impact on the welfare of the community in Cukir Village. The research employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. The results indicate that PG Tjoekir’s CSR initiatives are categorized into four main sectors: economy, socio-cultural, infrastructure, and health. In the economic sector, the company implements sugarcane farming partnerships and entrepreneurship training. However, employment through fixed-term contracts (PKWT) is excluded from CSR since it is part of the company’s operational activities governed by tax law No. 36 of 2008 and Company Law No. 40 of 2007. In the socio-cultural domain, the company supports religious and cultural events such as the Haul of Gus Dur and contributes to the construction of worship facilities. In the infrastructure sector, CSR contributions include road development and the normalization of 2,700 meters of irrigation canals. In the health sector, PG Tjoekir facilitates free medical services, fogging, and the distribution of food packages and vitamins to the community. Overall, these programs have had a positive impact on improving community welfare, although the benefits are not yet fully equitable and participatory. The study concludes that PG Tjoekir's CSR addresses key aspects of the Triple Bottom Line and Maqashid Shariah values. However, improvements are needed in transparency, impact evaluation, and community engagement to ensure inclusive and sustainable development.